Effects of combined infrared and hot-air drying on ginsenosides and drying characteristics of Panax notoginseng (Araliaceae) roots - Jiang, Dalong; Liu, Yue; Lin, Zifan; Wang, Wenjie; Zheng, Zhi'an (International Journal of Agricultural and Biological Engineering, 2022)
Exploring new drying technology can help to deal with the challenge of better preservation of rhizome medicinal materials in the traditional Chinese medicine industry. In current work, combined infrared and hot-air drying (IR-HAD) was employed to Panax notoginseng roots and its effect on drying kinetics, energy efficiency and quality, i.e., rehydration ratio (RR), color parameters (L*, a*, b*), total color difference (∆E), Panax notoginseng saponins (PNS) content, and ginsenosides content (R1, Rg1, Re, Rd, Rb1) were evaluated. Hot air drying (HAD) was used as the control. Results showed that the increase in drying temperature significantly shortened drying time and reduced energy consumption. The shortest drying time of 43.0 h and lowest specific energy consumption of 15.9 kW·h/(kg-water) were obtained by IR-HAD at 55°C. The decrease of radiation distance and the increase of radiation power led to the shortening of drying time. However, high drying temperature resulted in large ΔE values, large collapse structure, and RR of samples. The drying time of Panax notoginseng roots dried by IR-HAD at a drying temperature of 50°C was shorter (15.5%) than HAD dried at the same drying temperature. The contents of R1, Rg1, Re, Rb1, and PNS were higher when the samples were dried by IR-HAD than those dried by HAD at the same temperature of 50°C. Moreover, the IR-HAD dried samples shortened 15.5% drying time and saved 22.1% energy consumption compared with HAD. Therefore, the optimal process condition was Panax notoginseng roots under IR-HAD at drying temperature of 50°C, radiation distance of 12 cm and radiation power of 1350 W, which can shorten drying time, maintain high ginsenosides contents and satisfactory apparent qualities.Keywords: Panax notoginseng (Burk.) F. H. Chen (Araliaceae) roots, infrared and hot air drying, drying kinetics, energy consumption, qualityDOI: 10.25165/j.ijabe.20221501.6210Citation: Jiang D L, Zheng Z A. Effects of combined infrared and hot-air drying on ginsenosides and drying characteristics of Panax notoginseng (Araliaceae) roots. Int J Agric & Biol Eng, 2022; 15(1): 267–276.